THE LEGAL CERTAINTY OF PIERRE CARDIN BRAND RIGHTS HOLDERS IN INDONESIA IS LINKED TO LAW NUMBER 20 OF 2016 CONCERNING BRANDS AND GEOGRAPHICAL INDICATIONS - Budi Salim; Wiwik Sri Widiarty (International Journal of Artificial Intelligence Research, 2022)
One of the results of human work is the effort to create, or process something using tools and skills, until it becomes a new product. The role of brands is very important, especially in pursuing healthy business competition. The ability of a person named Pierre Cardin to produce designs – brand designs of various products that are loved by many people. In this study there are 2 (two) problem formulations, namely, 1). How is the legal certainty of a registered mark related to Law Number 20 of 2016 concerning Trademarks and Geographical Indications in connection with the pierre cardin brand dispute between the plaintiff and the defendant?. 2). What is the Decision of the Judiciary in relation to the trademark dispute between the plaintiff and the defendant in the pierre cardin case in Indonesia?. While the type of research method used is normative legal research, which is a research process to find a rule of law, legal principles, and legal doctrines to answer legal issues that are being faced. The resulting conclusions are: 1. The legal certainty of registered marks is associated with Law Number 20 of 2016 concerning Trademarks and Geographical Indications, in connection with the pierre cardin brand dispute between plaintiffs from Indonesia, and defendants from abroad, legal certainty is very clear from the 3 stages of pierre cardin lawsuits from commercial courts, cassations, and judicial review. 2. The judgments of the judicial bodies of the 3 legal judgments issued in connection with the pierre cardin suit there is one judgment that has a different opinion among the panel of judges, namely on the judgment of the cassation level.